Remittances and gender: Theoretical considerations and empirical evidence - Elke Holst; Andrea Schäfer; Mechthild Schrooten (Institute for the Study of Labor (IZA), 2011)
In this paper, we focus on network- and gender-specific determinants of remittances, which are often explained theoretically by way of intra-family contracts. We develop a basic formal concept that includes aspects of the transnational network and derive hypotheses from it. For our empirical investigation, we use data from the German Socio-Economic Panel Study (SOEP) for the years 2001-2006. Our findings show: first, the fact that foreign women remit less money than foreign men can be explained by the underlying transnational network contract. Second, remittances sent by foreigners and naturalized immigrants have at least partly different determinants. Acquiring German citizenship increases the probability of family reunification in the destination country and decreases remittances. Third, the structure of the existing social network in Germany and the network structure in the home country both play important roles in explaining remittances.
urn:nbn:de:101:1-201104113452
Keywords: F22; J16; D13; 330; remittances; gender; foreigners; naturalized migrants; Rücküberweisung (Migranten); Geschlecht; Familienökonomik; Ausländer; Staatsangehörigkeit; Schätzung; Deutschland